Inconsistent condom use by male clients during anal intercourse with occasional and regular female sex workers (FSWs): survey findings from southern states of India. Issue 11 (19th November 2014) - Ramanathan, Shreena; Nagarajan, Karikalan; Ramakrishnan, Lakshmi; Mainkar, Mandar K; Goswami, Prabuddhagopal; Yadav, Diwakar; Sen, Shrabanti; George, Bitra; Rachakulla, Harikumar; Subramanian, Thilakavathi; Paranjape, Ramesh S
Abstract : Objectives: Self-reported anal intercourse by female sex workers (FSWs) documented in recent studies from India range between 11.9% and 22%. However, comparable data on anal intercourse and condom use from male clients of FSWs is lacking. Using data from a bio-behavioural survey (2009–2010), we examined prevalence of anal intercourse, male clients' self-reported inconsistent condom use during anal intercourse with FSWs, and correlates of this behaviour in India's high HIV prevalence southern states (Andhra Pradesh, Maharashtra and Tamil Nadu combined). Methods: Using two-stage time location cluster sampling, we recruited 4803 clients of FSWs, ages 18–60 years, who had purchased sex from an FSW in the past month. After obtaining informed consent, respondents were interviewed and tested for HIV and sexually transmitted infections (syphilis, gonorrhoea and chlamydia). Logistic regression analysis was used to identify the factors associated with inconsistent condom use during anal intercourse (in the past 6 months) with FSWs. Results: Overall, 12.3% clients reported anal intercourse in the past 6 months, of whom 48.4% used condoms inconsistently. Clients of FSWs who were ages 26 years or older (AOR 2.68, p=0.032); employed as manual labourers (AOR 2.43, p=0.013); consumed alcohol (AOR 2.63, p=0.001); reported five or more sex acts with FSWs in the past month (AOR 2.53, p=0.031); and perceived themselves to be at higher risk for HIV (AOR 4.82, p=0.001) were more likely to inconsistently use condoms during anal intercourse. Conclusions: The results suggest that sex workers and their clients commonly practice anal intercourse, but a relatively high proportion of clients do not consistently use condoms, leading to a greater risk of acquiring HIV and its further transmission to other male and female sexual partners. Given the multidirectional risk, safer sex communication on heterosexual anal intercourse must be incorporated into HIV prevention programmes.